2017
DOI: 10.2319/060217-371.1
|View full text |Cite
|
Sign up to set email alerts
|

In vivo effect of antibacterial and fluoride-releasing adhesives on enamel demineralization around brackets: A micro-CT study

Abstract: Objectives: The aim of this in vivo study was to investigate the preventive effect of two different adhesives on enamel demineralization and compare these adhesives with a conventional one. Materials and Methods: Fifteen patients requiring the extraction of their first four premolars for orthodontic treatment were included in the study. One premolar was randomly selected, and an antibacterial monomer-containing and fluoride-releasing adhesive (Clearfil Protect Bond, Kuraray Medical, Okayama, Japan) was used fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…It found no significant differences among the adhesives regarding either the volume or depth of the WSLs. The results of the present study, which was long-term, were similar results to those of this short-term in vivo study [22].…”
Section: Discussionsupporting
confidence: 89%
“…It found no significant differences among the adhesives regarding either the volume or depth of the WSLs. The results of the present study, which was long-term, were similar results to those of this short-term in vivo study [22].…”
Section: Discussionsupporting
confidence: 89%
“…Although glass ionomer cements containing fluoride have been used as orthodontic adhesives, their bracket retention force is relatively low compared with that of conventional resin bonding [9]. Furthermore, studies on existing commercial fluoride-releasing adhesives and glass ionomers have revealed that they do not demonstrate a significant advantage in terms of their anti-demineralization effects compared with products that do not release fluoride [10]. To overcome these drawbacks, resin-modified glass-ionomer cements (RMGICs) have become the subject of various studies.…”
Section: Introductionmentioning
confidence: 99%
“…4 In recent years, new adhesives and primers that contain and release fluoride have entered the orthodontic market. 7,8 Previous studies showed that these fluoride-containing glass ionomer and composite adhesives decrease enamel decalcification around orthodontic brackets. 9,10 However, the fluoridecontaining and releasing adhesives and primers show their highest levels during the first weeks after bracket bonding.…”
mentioning
confidence: 99%